The Division of the Diocese of Beverley 1878, 'A Distasteful and Painful Affair'. Issue 1 (May 2014) - Turnham, Margaret
Abstract : The decision by the Holy See in 1878 to divide the diocese of Beverley into two smaller dioceses was unwelcome initially to many Catholics of the region, who felt it was unbalanced and unfair. This was a particularly long-held perception within the new diocese of Middlesbrough, which was comprised of the more rural areas of Yorkshire together with a new but often uneconomical industrial conurbation on the River Tees. The article examines whether this was an honest perception by scrutinising the logistics of the division, its geographical implications and the consequences for the future of the diocese in terms of the presbyterate and growth of mission.